Helping youth sport coaches integrate psychological skills in their coaching practice - Camire, M.; Trudel, P. (Qualitative Research in Sport, Exercise and Health, 2014)
Researchers have demonstrated the benefits of psychological skills training for athletes, but few studies have examined how coaches integrate such skills in their coaching practice. Empirical evidence indicates that the coaches have a preference to learn psychological skills in a user-friendly manner with consultant support. The purpose of the current study is to help youth sport coaches integrate psychological skills (leadership, goal-setting, self-awareness, visualisation) in their coaching practice. A sport psychology researcher worked with nine high school coaches from the sport of Canadian football during an entire season conducting interviews, workshops and observations. Findings indicated that the researcher was able to put in place an initiative that helped the coaches integrate psychological skills in their coaching practice. Generally, the coaches indicated that the partnership was beneficial but also mentioned how it could be improved in various ways. Findings are discussed using the current literature on youth development through sport and suggestions are offered to professionals working with youth sport coaches.